2017
DOI: 10.1038/s41598-017-04653-1
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and candidacidal activity of magnetic nanoparticles coated with cathelicidin LL-37 and ceragenin CSA-13

Abstract: Fungal infections caused by Candida spp. represent an emerging problem during treatment of immunocompromised patients and those hospitalized with serious principal diseases. The ever-growing number of fungal strains exhibiting drug resistance necessitates the development of novel antimicrobial therapies including those based on membrane-permeabilizing agents and nanomaterials as drug carriers. In this study, the fungicidal activities of LL-37 peptide, ceragenin CSA-13 and its magnetic derivatives (MNP@LL-37, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 55 publications
2
64
0
Order By: Relevance
“…Proposed nanostructures possess well-defined physicochemical properties and proven antibacterial activity. According to published literature [35][36][37], the proposed mode of antibacterial action of magnetic nanoparticles involves their contribution in the induction of oxidative stress, via generation of reactive oxygen species (ROS), as well as Our previous studies [38][39][40][41] have shown that they interact in a synergistic or additive manner, with chemotherapeutic agents used in standard antimicrobial treatment, as well as with a representative of antimicrobial peptides that take part in the immune-defense process and with their synthetic mimetics. Here we describe how the presence of magnetic nanoparticles might lead to improving the antimicrobial properties of artificial saliva substitutes ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed nanostructures possess well-defined physicochemical properties and proven antibacterial activity. According to published literature [35][36][37], the proposed mode of antibacterial action of magnetic nanoparticles involves their contribution in the induction of oxidative stress, via generation of reactive oxygen species (ROS), as well as Our previous studies [38][39][40][41] have shown that they interact in a synergistic or additive manner, with chemotherapeutic agents used in standard antimicrobial treatment, as well as with a representative of antimicrobial peptides that take part in the immune-defense process and with their synthetic mimetics. Here we describe how the presence of magnetic nanoparticles might lead to improving the antimicrobial properties of artificial saliva substitutes ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In turn, in the aspect of viability of cells embedded in biofilm mass, addition of tested substitutes supplemented by magnetic nanoparticles indicated that means reduction of viable cell was calculated at the level 55 % in the case of fungal cells, 40% in the case of Gram-positive bacteria and 50 % for P. aeruginosa (Figure 3d). Our previous studies [38][39][40][41] have shown that they interact in a synergistic or additive manner, with chemotherapeutic agents used in standard antimicrobial treatment, as well as with a representative of antimicrobial peptides that take part in the immune-defense process and with their synthetic mimetics. Here we describe how the presence of magnetic nanoparticles might lead to improving the antimicrobial properties of artificial saliva substitutes ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…This result was additionally confirmed by X-ray diffraction analysis and is in agreement with our previously published studies. 15,26 antimicrobial activity of 1,4-DhPs Antimicrobial activity was evaluated against representative strains of Gram-positive bacteria, Gram-negative bacteria and fungi. The analysis involved laboratory and clinical isolates of frequently occurring pathogenic strains including S. aureus, E. coli, P. aeruginosa, and Candida sp.…”
Section: Results Synthesis and Characterization Of Developed Nanosystemsmentioning
confidence: 99%
“…In a recent study, LL-37 or CSA-13 immobilized on magnetic nanoparticles were to shown to increase ROS generation in fungal cells, suggesting an additional pathway of antifungal activity with Candida spp. (Figure 3) [79]. Nevertheless, additional information is still required to fully understand how ceragenins target and kill fungal cells.…”
Section: Antifungal Activitymentioning
confidence: 99%